Mengintegrasikan Mekanisme Pencegahan (Ex-ante) dan Deterren (Ex-post) dalam Kepatuhan dan Penegakan Hukum Ketenagakerjaan: Pendekatan Komprehensif untuk Indonesia - Dicky Yulius Pangkey; Aga Kurniawan; Togi M. Mangunsong; Joemarthine Chandra; Faisal Santiago (JURNAL ILMIAH GEMA PERENCANA, 2026)
Employment law enforcement in Indonesia is caught in a dilemma between legal certainty and social justice. This article identifies compliance challenges, analyzes the relevance of preventive (ex-ante) and remedial (ex-post) mechanisms, and formulates an integrative model based on responsive regulation. The study uses qualitative method with a normative juridical approach with a comparative analysis of practices in Australia, the United Kingdom, and South Korea, and a review of Indonesian labor inspection data from 2023. The results indicate that law enforcement remains ineffective due to limited supervisory capacity, low legal awareness, and unequal industrial relations. Ex-ante mechanisms (such as education and compliance certification) can prevent violations, while ex-post mechanisms (such as progressive sanctions) ensure accountability. Integrating the two within a responsive regulatory framework balances voluntary compliance with credible deterrence. The study recommends five strategic steps: (1) reforming and digitizing the inspection system; (2) establishing a National Labor Compliance Commission; (3) revising Government Regulation No. 35/2021 to include ex-ante instruments; (4) strengthening the capacity of trade unions and employer organizations; and (5) improving the Industrial Relations Court with class action and fast-track mechanisms. This integration provides a normative foundation for a more responsive, fair, and adaptive labor law system in Indonesia.